Sosiologi Pembangunan dan Ruang Lingkupnya - Azmiatul Khairiyah; Sonia Muliani; Akdila Bulanov (Kampus Akademik Publiser, 2026)
This study aims to present the sociology of development and its scope through a systematic literature review (SLR) approach. The sociology of development is defined as a branch of sociology specifically examining social change in relation to economic, political, social, educational, and religious development. The sociology of development and its scope are important to study because they aim to understand changes in social structures and institutions as a result of planned and directed development processes. A literature search was conducted through databases, Google Scholar, and Google Books, covering publication years 2021-2026. Based on the stages of identification, screening, eligibility, and included studies, 15 relevant articles were identified for analysis. The results indicate that the sociology of development and its scope is a social science that studies development processes in society from economic, social, political, educational, and religious perspectives.